Interdecadal Increase in Summertime Extreme Precipitation over East China in the Late 1990’s - Zang, Zengliang; Luo, Junyao; Ha, Yao (Frontiers in Earth Science, 2022)
This study focuses on the interdecadal increase of summertime extreme precipitation over East China in the late 1990s and physical mechanisms behind. The results show that summer extreme precipitation over East China during 1979–2020 demonstrates an upward trend and a significant interdecadal increase occurs around 1997/1998. Since 1997, extreme precipitation anomalies turn from less than normal to more than normal, corresponding to a strong upward movement in the lower troposphere over East China. A cyclonic circulation with positive vorticity controlled by a strong southeasterly flow appears in the lower level over South China. The reasons for the interdecadal increase of summer extreme precipitation over East China are analyzed from the perspective of the abnormally strong South Asian subtropical high (SAH) and the atmospheric circulation anomalies caused by zonal sea surface temperature (SST) gradient in the tropical oceans. After 1997, positive sensible heat anomalies appear over the Tibetan Plateau in spring, which is the major factor that maintains the intensity of the SAH. Besides, the SST of the tropical oceans presents an obvious “high-low-high” zonal gradient distribution with positive sea surface temperature anomaly (SSTA) in the Indian Ocean and western Pacific, and negative SSTA over the Maritime Continent. The zonal SST gradient results in an anomalous downdraft and boundary layer divergence over the Maritime Continent. The tropical zonal SST gradient triggers a local Hadley circulation, and its ascending branch is located in East China. This is a circulation condition favorable for the development of extreme precipitation. In addition, since the late 1990s, the SAH has strengthened in the upper troposphere above the southeastern China. The anomalous divergence at the upper level effectively maintains the upward movement, which in turn facilitates the occurrence of extreme precipitation. As a result, the sensible heat changes in the Tibetan Plateau in spring and the tropical SST zonal gradient jointly affect summer extreme precipitation over East China, leading to the interdecadal increase of extreme precipitation in the late 1990s.